If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(3b + 3) + (22b + -4) = 0 Reorder the terms: -7(3 + 3b) + (22b + -4) = 0 (3 * -7 + 3b * -7) + (22b + -4) = 0 (-21 + -21b) + (22b + -4) = 0 Reorder the terms: -21 + -21b + (-4 + 22b) = 0 Remove parenthesis around (-4 + 22b) -21 + -21b + -4 + 22b = 0 Reorder the terms: -21 + -4 + -21b + 22b = 0 Combine like terms: -21 + -4 = -25 -25 + -21b + 22b = 0 Combine like terms: -21b + 22b = 1b -25 + 1b = 0 Solving -25 + 1b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 1b = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 1b = 0 + 25 1b = 0 + 25 Combine like terms: 0 + 25 = 25 1b = 25 Divide each side by '1'. b = 25 Simplifying b = 25
| 9(2x-6)=3(6x+5) | | n-3n=-14-4n | | 9+3z-3=9z+12-3z | | 9+3z-3=9z+122-3z | | 3.9q-1.9-4.3q=-1.4q-5.5 | | 5(5+t)-3(t-6)= | | x(5x+1)(x-9)=0 | | 3(2n-7)+7(4-2n)= | | x^2-6x+20=0 | | 124-6x=21x+16 | | 3/2(5x-2)=x | | 3(x+4)+2(5x+2)= | | 6x+7+3x+1= | | -4x+5=5-4x | | -3y+6=-4y+7 | | 7xy-xy+3xy= | | 4w-5+9w+2= | | -4+5=5-4x | | 20-x=10x-2 | | 3x-(2x+9)=4x-27 | | 87-5x=40x+22 | | x+(x+27)+(3x-24)=633 | | -14-4x=13-7x | | 4a^2-9b^2=0 | | 4m^2-9k^2=0 | | 11n-14= | | 2x-6=8x-24 | | x+7(4)=16 | | 12k+9=0 | | 9+6r-4=9r+14-2r | | m^4-4m^3+7m^2-4m+6=0 | | m^7+m^5= |